The Impact of Anterior Spondylolisthesis and Kyphotic Alignment on Dynamic Changes in Spinal Cord Compression and Neurological Status in Cervical Spondylotic Myelopathy: A Radiological Analysis Involving Kinematic CT Myelography and Multimodal Spinal Cord Evoked Potentials. Issue 2 (15th January 2021) - Sakamoto, Takuya; Funaba, Masahiro; Imajo, Yasuaki; Nagao, Yuji; Suzuki, Hidenori; Nishida, Norihiro; Fujimoto, Kazuhiro; Sakai, Takashi
Abstract : Study Design: A retrospective study of prospectively collected data. Objective: This study aimed to examine how radiological parameters affect dynamic changes in the cross-sectional area of the spinal cord (CSA) in cervical spondylotic myelopathy (CSM) patients and how they correlate with the severity of myelopathy, by evaluating multi-modal spinal cord evoked potentials (SCEPs). Summary of Background Data: Appropriate assessments of dynamic factors should reveal hidden spinal cord compression and provide useful information for choosing surgical procedures. Methods: Seventy-nine CSM patients were enrolled. They were examined with kinematic CT myelography (CTM), and the spinal levels responsible for their CSM were determined via SCEP examinations. The C2–7 angle, C2–7 range of motion, and percentage of slip were measured on the midsagittal view during flexion and extension, and the CSA was measured on the axial view in each neck position using kinematic CTM. The patients who exhibited the smallest CSA values during extension and flexion were classified into Groups E and F, respectively. Results: Fifty-two (65.8%) and 27 (34.2%) cases were included in Groups E and F, respectively. The preoperative JOA score did not differ significantly between the groups; however, the preoperative lower-limb JOA score of Group F was significantly lower than that of Group E (2.24 ± 0.82 vs. 2.83 ± 1.09, P  = 0.016). In the multiple logistic regression analysis, a small C2–7 angle during extension (β = 5°, odds ratio: 0.69, 95% confidence interval [CI]: 0.54–0.90) and the slip percentage during flexion (β = 5%, odds ratio: 1.42, 95% CI: 1.09–1.85) were identified as significant predictors of belonging to Group F. Conclusion: Exhibiting more severe spinal cord compression during neck flexion was associated with a small C2–7 angle and anterior spondylolisthesis. The neurological status of the patients in Group F was characterized by severe lower limb dysfunction because of a disturbed blood supply to the anterior column. Level of Evidence: 4 Abstract : Exhibiting more severe spinal cord compression during neck flexion was associated with a small C2-7 angle and anterior spondylolisthesis. The neurological status of the patients in Group F was characterized by severe lower limb dysfunction because of a disturbed blood supply to the anterior column.